Colorectal Cancer in a 17-Year-Old Boy: A Case Report - Febi Iswandi; Rizky E. Asri; Nur Fitriany Lihawa; Dewandaru Istighfaris A.B (Universitas Negeri Gorontalo, 2023)
Introduction: Colorectal cancer is the fifth most common malignant neoplasm worldwide. Commonly found in adults, the adolescent population is scarce. Colorectal cancer diagnosed and treated late is potentially associated with the worst prognosis.Case: A 17-year-old boy was admitted to the hospital due to a distended abdomen and abdominal pain, nausea, and vomiting that he had been experiencing seven days prior. The patient neither had a bowel movement nor flatus for the day. Abdominal ultrasound showed a regional intraluminal mass on the right upper quadrant with a suspicion of an appendical mass with a differential diagnosis of intussusception, colon tumor, and obstructive ileus. Acute abdominal series showed small bowel obstruction. When the surgery was performed, there was a tumor in the hepatic flexure of the colon. Histopathological examination revealed colon adenocarcinoma.Conclusion: The incidence of colorectal cancer in adolescents has increased. Right extended hemicolectomy was performed in this case, but the patient refused the chemotherapy. The patient was readmitted to the hospital five months later, was only given palliative therapy in the Intensive Care Unit, and died two weeks later. We believe that had the chemotherapy been performed, the patient might have had a better prognosis. This case report will help increase awareness among doctors and surgeons in including colorectal carcinoma as a differential diagnosis in adolescents so that it can shorten the delay in diagnosis, which in turn will endanger the patient's prognosis.Keywords: Colorectal cancer; Adenocarcinoma; Adolescents